Karya Graffiti sebagai Representasi Persoalan Sosial di Kota Bandung - Aris Darisman (Bina Nusantara University, 2014)
Graffiti works are often found in urban area, so it becomes culture expression of a city represented through art (urban art). At this stage, graffiti is classified in the genre of street art. There is high enough desire for graffiti artists to interact and convey their message through their works with public. Thus, public spaces, such streets, become a choice for space and inspiration to them to work as well as exhibitions. Everyday issues, which according to Charles Baudelaire (1863), become inspiration for impressionist painters to paint modern subjects. Modern subjects in the form of everyday problems occur along the way in Paris, bridges, and roadside cafes. What was disclosed by Baudelaire is still factual at present, that the road becomes the source of inspiration collection. This study used field research, literature studies, and interview. Meanwhile, research object was graffiti works in Bandung. Research showed street art, in this case graffiti, was a symbol of resistance and response to actual political conditions. Walls and other objects commonly found in the street or public space were a stretch of ideas and canvas for graffiti artists.